THE MYSTERY OF HUMAN PERSON: : MYSTICAL ANTHROPOLOGY IN HAMZAH FANSURI’S SHA‘ĪR - Laksana, A. Bagus (Kanz Philosophia A Journal for Islamic Philosophy and Mysticism, 2016)
This essay endeavors to look closely at the mystical theological anthropology of Hamzah Fansuri, the first and one of the greatest Sufi writers in the Malay world. Mystical anthropology is arguably the underlying theme of all Fansuriâ€™s poems and he develops this mystical discourse on the theomorphic dignity of every human person, together with the dynamic of return to God, by using some quite original imageries and symbolisms of his own. However, Fansuriâ€™s mystical theological anthropology belongs to the tradition of Ibn al-â€˜ArabÄ« (the WujÅ«diyyah doctrine), while his works also betray familiarity with and the influence of other great mystics of Islam, such as â€˜Aá¹á¹Är and á¸¤Äfiáº“.